PemBla: a Phase 1 study of intravesical pembrolizumab in recurrent non-muscle-invasive bladder cancer - Woodcock, VK; Chen, J-L; Purshouse, K; Butcher, C; Collins, L; Haddon, C; Verrall, G; Elhussein, L; Roberts, C; Tarlton, A; Rei, M; Napolitani, G; et al. (Wiley, 2023)
Objectives: This study aimed to investigate the anti-PD-1 inhibitor pembrolizumab as a potential agent for use in non-muscle-invasive bladder cancer (NMIBC) by conducting a Phase 1 safety run-in study to assess the safety and tolerability of intravesical pembrolizumab after transurethral resection of the bladder tumour (TURBT).